Baltic Subjects of the Russian Federation among Border Regions of Russia - Klemeshev, Andrey P.; Fedorov, Gennady M.; Manakov, Andrey G. (International Journal of Economics and Financial Issues, 2015)
Frontier location of the regions is an ambiguous and often-changing factor in their development. It is therefore of particular importance to undertake a comparison of the border regions with the internal – inland regions, typologize and evaluate each type. The purpose of this article is to assess the level of economic development of the border regions of the Russian Federation located in the Baltic Sea region as compared to other frontier regions of Russia. Paper identifies their place among border regions of the Russian Federation, allocates the key problems and prospects of development in relation to the benefits being used and drawbacks of their geographical location being neutralized. In the course of research, the theoretical and empirical methods for the typology of regions were used. The features and possibilities for further development of the Baltic border regions of the Russian Federation are defined in accordance with their socio-economic type, which reflects their place in the domestic and international territorial division of labor. Keywords: border regions, frontier regions, inland regions, hinterland, borderland, Baltic region, Russia JEL Classifications: F5; F6; R1